2022
DOI: 10.1111/bcp.15252
|View full text |Cite
|
Sign up to set email alerts
|

Using Japanese big data to investigate novel factors and their high‐risk combinations that affect vancomycin‐induced nephrotoxicity

Abstract: Aims Several factors related to vancomycin‐induced nephrotoxicity (VIN) have not yet been clarified. In the present study, we used Japanese big data to investigate novel factors and their high‐risk combinations that influence VIN. Methods We employed a large Japanese electronic medical record database and included patients who had been administered intravenous vancomycin between June 2000 and December 2020. VIN was defined as an increase in serum creatinine ≥0.5 mg/dL or 1.5‐fold higher than the baseline. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
(149 reference statements)
0
10
0
Order By: Relevance
“…Database We used RWD database of the Health, Care and Education Information Evaluation and Promotion Institute (HCEI; Kyoto, Japan) with assistance from Real World Data Co., Ltd. (Kyoto, Japan) to collect anonymized medical information derived from electronic medical records. 14) The RWD database contained electronic medical records and claims data of approximately 20 million people from 160 medical institutions. 14,15) Included Patients Our study included VCM-administered and hospitalized patients with estimated age range of 0-1 year between June 2000 and December 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Database We used RWD database of the Health, Care and Education Information Evaluation and Promotion Institute (HCEI; Kyoto, Japan) with assistance from Real World Data Co., Ltd. (Kyoto, Japan) to collect anonymized medical information derived from electronic medical records. 14) The RWD database contained electronic medical records and claims data of approximately 20 million people from 160 medical institutions. 14,15) Included Patients Our study included VCM-administered and hospitalized patients with estimated age range of 0-1 year between June 2000 and December 2020.…”
Section: Methodsmentioning
confidence: 99%
“…In 2000, a case report of two patients who had taken a diuretic, angiotensin receptor blocker, and non-steroidal anti-inflammatory drug (NSAID) in combination, so-called “triple whammy,” and experienced a rise in SCr was published ( Thomas, 2000 ). Subsequently, a number of clinical studies worldwide have investigated whether concurrent use of these drug classes increases SCr level and decreases estimated glomerular filtration rate ( Loboz and Shenfield, 2005 ; Lapi et al, 2013 ; Camin et al, 2015 ; Kunitsu et al, 2019 ; Imai et al, 2022 ). Besides the triple whammy, clinical studies have tried to detect drug-drug interactions between two or more drug classes in acute kidney injury ( Bird et al, 2013 ; Gandhi et al, 2013 ; Gul et al, 2016 ; Inaba et al, 2019 ; Okada et al, 2019 ; Liu et al, 2021 ; Salerno et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…9 More recently, an investigational study performed using Japanese big data sets demonstrated that compared with the concentration range of 15–20 mcg/mL (OR 2.587, 95% CI 2.149–3.114), vancomycin trough concentrations of ≥20 mcg/mL were significant independent factors affecting vancomycin-induced nephrotoxicity. 10…”
Section: Introductionmentioning
confidence: 99%
“…9 More recently, an investigational study performed using Japanese big data sets demonstrated that compared with the concentration range of 15-20 mcg/mL (OR 2.587, 95% CI 2.149-3.114), vancomycin trough concentrations of $20 mcg/mL were significant independent factors affecting vancomycin-induced nephrotoxicity. 10 In this study, we aimed to develop and evaluate a novel software program, SAKURA-TDM ver.1.0 for AUC-guided vancomycin dosing. We also attempted to determine the theoretical cutoff point of steady-state AUC 24 , which could lower the probability of trough values exceeding 20 mcg/mL at the next blood sampling.…”
Section: Introductionmentioning
confidence: 99%